Clinical staging in amyotrophic lateral sclerosis: analysis of Edaravone Study 19. Issue 2 (27th October 2020) - Al-Chalabi, Ammar; Chiò, Adriano; Merrill, Charlotte; Oster, Gerry; Bornheimer, Rebecca; Agnese, Wendy; Apple, Stephen
Abstract : Objective: This was a post hoc analysis of the Edaravone Phase III Study MCI186-19 ('Study 19') to examine the utility of clinical staging systems as end points in clinical trials in amyotrophic lateral sclerosis (ALS). Methods: Amyotrophic Lateral Sclerosis Functional Rating Scale—Revised item scores from Study 19 were retrospectively mapped to King's stage and Milano-Torino staging (MiToS) stage. We assessed the percentage of patients who experienced progression in King's and MiToS stages during Study 19. We also assessed disease progression in subgroups of patients according to baseline King's stage. Results: During double-blind treatment, the percentage of patients who experienced a progression in King's stage was lower for edaravone (42.0%, 95% CI 30.4% to 53.6%) than placebo (55.9%, 95% CI 44.1% to 67.6%). The most pronounced effect was noted among patients who were in stage 1 and was maintained throughout open-label treatment. An analysis of a ≥2-stage progression in MiToS stage showed no difference between treatment arms during double-blind treatment, but during the open-label period, more rapid progression was noted among patients in the placebo–edaravone arm than among those in the edaravone–edaravone arm (log-rank test, p<0.001). Conclusions: The King's and MiToS staging systems provided utility in assessing clinical progression in Edaravone Study 19. These findings may support the use of staging systems as end points in ALS clinical trials and to understand the timing of benefit as measured by these scales.